Analysis Mathematical Concept Understanding Ability in Grade V Student in Geometry Material - An Nissa Putri, Shiva Stevanya; Suwandayani, Beti Istanti; Deviana, Tyas (Universitas Negeri Padang, 2024)
This study was motivated by the low understanding of mathematical concepts in students. This study aims to analyze the ability to understand mathematical concepts of geometry material in grade V students. This type of research is descriptive quantitative research. The instruments used were tests, semi-structured interviews, and classroom observations. The results showed that the ability to understand concepts in class V students was low, which was shown based on the test results with the results of 3 students in the high category, 6 students in the medium category, and 2 students in the low category. Factors influencing this low understanding include less varied teaching methods, lack of visual aids, learning resource support, and lack of student motivation. This study contributes to educators in improving geometry teaching methods with more variety and involving relevant visual aids, as well as motivating students, to improve better concept understanding in elementary school students